2002
DOI: 10.1037/0882-7974.17.4.548
|View full text |Cite
|
Sign up to set email alerts
|

The role of cognitive stimulation on the relations between age and cognitive functioning.

Abstract: To make a convincing argument that cognitive stimulation moderates age trends in cognition there must be (a) a negative relation between age and level of cognitive stimulation, (b) a positive relation between level of cognitive stimulation and level of cognitive functioning, and (c) evidence of an interaction between age and cognitive stimulation in the prediction of cognitive functioning. These conditions were investigated in a study in which 204 adults between 20 and 91 years of age completed an activity inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
130
2
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(141 citation statements)
references
References 28 publications
(41 reference statements)
6
130
2
3
Order By: Relevance
“…However, some previous studies have not supported the use-it-or-lose-it hypothesis (e.g., Salthouse, Berish, & Miles, 2002). In line with Salthouse's hypothesis (2006), that of preserved differentiation, some studies have found no influence of activity on cognitive functioning or found an influence in the opposite direction of cognitive performance on activity.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…However, some previous studies have not supported the use-it-or-lose-it hypothesis (e.g., Salthouse, Berish, & Miles, 2002). In line with Salthouse's hypothesis (2006), that of preserved differentiation, some studies have found no influence of activity on cognitive functioning or found an influence in the opposite direction of cognitive performance on activity.…”
Section: Introductionmentioning
confidence: 62%
“…In line with Salthouse's hypothesis (2006), that of preserved differentiation, some studies have found no influence of activity on cognitive functioning or found an influence in the opposite direction of cognitive performance on activity. Salthouse, Berish, and Miles (2002) did not find any evidence for activity mediated, age-related differences in spatial ability, reasoning, vocabulary, and episodic memory. Hultsch, Hertzog, Small, and Dixon (1999) found that changes in activity levels over 6 years were not associated with corresponding changes in cognitive performance, including episodic memory, vocabulary, 6 reading comprehension, and verbal fluency.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…An important focus of much research in cognitive gerontology has been on the identification of possible factors associated with slower rates of decline, with some significant results (e.g., see Hawkins, Kramer, & Capaldi, 1992, on aerobic exercise; Lövdén, Ghisletta, & Lindenberger, 2005, on social participation) but also some null effects (e.g., see Rabbitt, Chetwynd, & McInnes, 2003, on intellectual ability and socio-economic status; Salthouse, Berish, & Miles, 2002, on cognitive stimulation). One factor that has so far "received little attention" (Meinz & Salthouse, 1998) is that of gender.…”
Section: Introductionmentioning
confidence: 99%
“…Two constructs often presumed to require executive contributions are switching between tasks (task switching) and carrying out two tasks simultaneously (time sharing). In earlier investigations, Salthouse and Miles (2002) and Salthouse and colleagues (1998) had found that latent variables measuring task switching and time sharing could be distinguished from other constructs, although the relationships between these constructs, age, and other constructs were largely shared. Following a research strategy described by Salthouse (2001a), Salthouse et al (2003) tested whether age-related variance in various measures was mediated through a second-order construct of executive function, which in turn comprised distinct constructs of updating (similar to switching), time sharing, and inhibition of distracting information.…”
Section: B Common Cause Modelsmentioning
confidence: 99%